2017
DOI: 10.29359/bjhpa.09.3.02
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic analysis of the block start and 20-metre acceleration phase in two highly-trained sprinters: A case report

Abstract: Open Access License:This is an open access article distributed under the terms of the Creative Commons Attribution-Non-commercial 4.0 International (http://creativecommons.org/licenses/by-nc/4.0/), which permits use, distribution, and reproduction in any medium, provided the original work is properly cited, the use is non-commercial and is otherwise in compliance with the license. abstract BackgroundThe main purpose was to evaluate individual kinematic characteristics in highly trained sprinters during the "se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Other technologies have been used, although caution must be applied to data from currently available laser [96] and global positioning system (GPS) [97] devices during early acceleration. Inertial measurement units offer a theoretically promising option for relatively noninvasive data collection during training [98]. However, the error in such data must be critically considered in the context of the smallest meaningful differences for understanding sprint start technique, particularly given the magnitudes of random measurement error previously reported [99, 100].…”
Section: Other Considerationsmentioning
confidence: 99%
“…Other technologies have been used, although caution must be applied to data from currently available laser [96] and global positioning system (GPS) [97] devices during early acceleration. Inertial measurement units offer a theoretically promising option for relatively noninvasive data collection during training [98]. However, the error in such data must be critically considered in the context of the smallest meaningful differences for understanding sprint start technique, particularly given the magnitudes of random measurement error previously reported [99, 100].…”
Section: Other Considerationsmentioning
confidence: 99%
“…In a study of Janowski et al, 10 it was aimed to evaluate individual kinematic characteristics in highly trained sprinters during the "set" position, block clearance and a 20-m acceleration phase; it was concluded that fast block clearance and stride symmetry are key factors affecting sprint performance during the 20-m acceleration phase. Despite these results, it is important to mention that rapid clearance not always mean that high levels of force or power are being exerted on starting blocks.…”
Section: Discussionmentioning
confidence: 99%
“…According to the characteristics of the sprinters and the specificity of the start from starting blocks, it seems that a quick start off is a key factor for the performance in the first 20 meters (20-m) of sprint. 10 However, the maximal isometric force (MIF) on starting blocks and its relation to performance in the first few meters of the sprint has not been evaluated. 10 To help with these relation, there are functional electromechanical dynamometers (FEMDs) that allow to execute evaluation in similar conditions from competition, specifically in vector planes and muscular contractions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation